The Effect of Evaluation by the Chairman on The Performance of Nurses in Investigations in Medan Haji General Hospital - Rian Alfian; Arifah Devi Fitriani; Beni Satria (Newinera Publisher, 2021)
The purpose of this study is to determine the effect of evaluation by the head of the room on the performance of nurses in the inpatient room of RSU Hajj Medan in 2020. This study used a quantitative method with a cross sectional design. The results of the study found that the effect of behavior evaluation on nurse performance showed a significance value of 0.000 (p <0.05). The effect of the evaluation of professional abilities on the performance of nurses shows a significance value of 0.417 (p> 0.05). The effect of the evaluation of the nursing process on the performance of nurses shows a significance value of 0.006 (p <0.05). The conclusion of this study is that there is an effect of behavior evaluation and nursing process by the head of the room on the performance of nurses in the inpatient room of RSU Hajj Medan in 2020. Evaluation of professional abilities does not have a significant effect on the performance of nurses. The most influential variable is the behavior with the highest coefficient value, amounting to 0.512 with a positive value. The head of the room is expected to optimize his role in evaluating programmed, scheduled, and in accordance with the standards and principles of implementation.